1997
DOI: 10.1093/jn/127.7.1371
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Semistarvation and Streptozotocin-Diabetes in Rats Have Different Effects on the In Vivo Glucose Uptake by Peripheral Tissues in Their Female Adult Offspring

Abstract: Previous work in humans and rats has revealed a link between perinatal growth retardation and glucose intolerance in adulthood. Both maternal semistarvation and severe diabetes are accompanied by perinatal growth retardation in rats. In this study, we compared the effect of these conditions on tissue glucose uptake in their female offspring. Glucose uptake was measured as glucose metabolic index (GMI), using 2-deoxy-[1-3H]-glucose, in the postabsorptive state and during euglycemic hyperinsulinemia. The GMI was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 27 publications
10
50
1
Order By: Relevance
“…16 Basically, similar observations have been made in sheep, although at different times postnatally, giving a strong support to the hypothesis that both low insulin secretion and insulin resistance contribute to impair glucose homeostasis after IUGR.…”
Section: Effects Of Intrauterine Growth Retardation In Animal Modelsupporting
confidence: 70%
See 1 more Smart Citation
“…16 Basically, similar observations have been made in sheep, although at different times postnatally, giving a strong support to the hypothesis that both low insulin secretion and insulin resistance contribute to impair glucose homeostasis after IUGR.…”
Section: Effects Of Intrauterine Growth Retardation In Animal Modelsupporting
confidence: 70%
“…Intrauterine growth retardation (IUGR) can be induced in experimental animal models by energy restriction, 16 or by feeding an isoenergetic low-protein diet [17][18] during pregnancy. Decreased foetal nutritional delivery can also be induced by ligation of uterine arteries of pregnant rats.…”
Section: Effects Of Intrauterine Growth Retardation In Animal Modelmentioning
confidence: 99%
“…The biochemical mechanism results in mammalian cell death. Streptozotocin prevents cellular reproduction with a much smaller dose than the dose needed for inhibiting the substrate connection to the DNA or inhibiting many of the enzymes involved in DNA synthesis (10). Although Streptozotocin prevents entry of cells into mitosis but no special phase of the cellular cycle is especially sensitive to its mortal effects.…”
Section: Resultsmentioning
confidence: 99%
“…If the environment of the rats is kept clean, there will be a change of color from white to pink. Otherwise, the change will be from white to gray (10). Pancreatic biopsy of normal and diabetic rats confirmed that the islet cells were Table.1 Shows data …”
Section: Induction Of Diabetes By Streptozotocinmentioning
confidence: 91%
“…This may be due to STZ impairs liver function, thus leading to leakage of these enzymes in the blood by STZ due to prevention of DNA synthesis in mammalian cells and prevents cellular reproduction by inhibiting the substrate binding to the DNA or inhibiting many of the enzymes involved in DNA synthesis [60]. Waer and Helmy [61] revealed that, diabetic hepatic injuries results from several agents and is not controllable only via inhibition of hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%